The effect of interactive online learning on knowledge, attitude, and practice related to diabetes mellitus of productive-age population - Bendix Samarta Witarto; Visuddho Visuddho; Teddy Yusuf; Rizqi Apsari Fairuz Kamila; Ghifar Akbar Iftinan; Clonia Milla; Salma Firdaus; Muhammad Wildan Nabalah Hartawan; Aisha Fairuz Zahira; Lintang Cahyaning Ratri; Amara Destania Armyne; Sulistiawati Sulistiawati; Rimbun Rimbun (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: Diabetes mellitus still becomes a significant population health problem. In achieving sufficient awareness, face-to-face public education methods may serve as an effective measure. However, in the amid of pandemic, their implementation is restricted, which leads to the use of virtual platforms for learning activities. In addition, the applicability of the online learning method has yet to be explored.Objective: To evaluate its impact on the knowledge, attitude, and lifestyle practices of the productive-age population related to diabetes.Methods: A pre-test and post-test quasi-experimental study involving a single group was conducted among the productive-age population (aged 15 to 64 years) selected using consecutive sampling in two sub-districts in Surabaya, Indonesia. Baseline and endline levels of participants’ knowledge, attitude, and practice regarding diabetes assessed using a self-developed questionnaire were compared after receiving an educational intervention.Results: A total of 19 participants meeting the eligibility criteria were selected as the study subjects. A statistically significant increase in the participants’ knowledge score from pre- to post-test (p=0.038) was observed. There was no significant change between the pre-test and post-test scores of attitude (p=0.938) and practice (p=0.087) after the intervention.Conclusion: Online learning method improved the population’s knowledge regarding diabetes mellitus. However, it appears to have a limited role in providing better modification for attitude and practice. Further research comparing online and traditional face-to-face education methods are required to establish this approach as an alternative.